Negative campaigning in European parliamentary elections: the case of Portugal 2009 - 2019 - Fonseca, André Filipe Correia Santana da (2019)
This study aimed to contribute to the literature on negative campaigning, by studying it on a never tested context: the campaigning to the European Parliament elections (second-order elections) in Portugal during 2009 to 2019. The main objective of this dissertation was to verify patterns of evolution along the period and test the conventional factors explaining campaign negativity outside a first-order electoral competition. In order to fulfil this goal, a content analysis approach was used. The focus was put on the political discourse on TV spots and outdoors. The results show that during this period campaign negativity fluctuated, being the 2014 campaign the one with more negativity, which is in accordance with many studies in the European context. Other conclusions of the study are that parties’ position on the polls tend to influence the amount of negativity used. Also, the use of this strategy is mostly seen at the beginning of campaigns, contrary to what the literature suggests, and ideology affects the level of negativity, being the most left-wing parties the more negative. Most of the campaign is focused on national policies and not European issues.